Analysis of Psychological Contract, Job Satisfaction, and Organizational Commitment In Improving Employee Performance at Pegadaian UPC Perum Bumi Dalung - Ni Nyoman Wulan Antari; Sindyawati Rari Duli Goran Tokan (Green Publisher Indonesia, 2026)
This study aims to analyze the influence of psychological contracts, job satisfaction, and organizational commitment on employee performance at Pegadaian UPC Perum Bumi Dalung. The research background is based on the importance of human resource management in enhancing organizational effectiveness, particularly through fulfilling employee expectations, creating job satisfaction, and strengthening commitment to the organization. A quantitative approach is employed, involving 78 respondents as the sample. Data were collected through questionnaires that had been tested for validity and reliability and then analyzed using multiple linear regression. The research findings indicate that the three independent variables—psychological contract, job satisfaction, and organizational commitment—have a positive and significant impact on employee performance. A fulfilled psychological contract enhances employee motivation and contributions, high job satisfaction boosts productivity and loyalty, and strong organizational commitment strengthens individual dedication and performance. These findings confirm that psychological and social aspects in work relationships play a crucial role in improving employee performance. This research contributes practically to Pegadaian's management in formulating more effective human resource management strategies and academically enriches the literature on factors influencing employee performance. Thus, maintaining psychological contracts, enhancing job satisfaction, and strengthening organizational commitment become crucial keys to driving organizational success.